Hubungan Pengetahuan Ibu Menopause Usia 40-58 Tahun Dengan Penyakit Osteoporosis Di Desa Lot Kala Kebayakan Kecamatan Kebayakan Kabupaten Aceh Tengah - Hudnah, Hudnah; Nurrahmah, Riska; Zakiyah (Universitas Prima Indonesia, 2024)
Menopause is the last spontaneous menstrual period in a woman and is a diagnosis established retrospectively after amenorrhea during the 12 months of menopause. Osteoporosis is a disease with the main sign of reduced bone density, which results in increased bone fragility and increases the risk of bone fractures. Knowledge is the result of knowing, and this occurs after people sense a particular object. The aim of this research is to determine the relationship between knowledge of menopausal mothers aged 40-58 years and osteoporosis in Lot Kala Kebayakan Village, Kebayakan District, Central Aceh Regency. This type of research is analytical research with a cross sectional design approach. The population in this study were all menopausal mothers aged 40-58 years in Lot Kala Kebayakan village, namely 210 respondents. This study used random sampling technique with a total of 68 respondents. Data analysis in research uses the Chi-Square statistical test. The results of the analysis of mothers' knowledge of menopause and osteoporosis obtained a P value = 0.003. The results of this research are that there is a relationship between maternal knowledge of menopause and osteoporosis in Lot Kala village, most sub-districts, Central Aceh district. Suggestions for future researchers can be made by comparing various other factors related to osteoporosis in menopausal mothers. Keywords: Menopause, Osteoporosis, Knowledge